Market Participation of the Local People in Non-timber Forest Products (NTFPs) in Omo Forest Reserve, Nigeria (2017)
Marketing systems for non-timber forest products (NTFPs) have evolved over centuries and are culturally rooted in the traditional practices of local people. Relative to timber marketing, marketing of NTFPs has received little attention. This study assessed the NTFPs market participation behavior of people living in Omo Forest Reserve, Ogun State, Nigeria. Primary data were collected from 192 respondents using a multistage sampling procedure and were analyzed using descriptive statistics and a Heckman model. The decision to participate in NTFPs marketing increases with being a female, larger households, greater number of males and females aged 15–64, higher dependency ratios, and being married. Conversely, it decreases with older collectors, higher educational attainment, engagement in farming activities, higher non-farm income, higher per capita land size and farther market distance. Level of market participation was found to be positively and significantly influenced by being married, income from NTFPs, membership of forest users’ association and forest conservation. It is negatively and significantly influenced by being a male, age, household size, education level, livelihood diversification, non-farm income, transportation cost, per capita land size and average market distance.